Knowledge and attitude of pregnant women towards modes of delivery in an antenatal care clinic in Baghdad - Nasir, Nadia A.; Amir, Hind (Journal of the Faculty of Medicine Baghdad, 2017)
Background: Since 1985 the World Health Organization (WHO) had stated: “There is no justification for any region to have Caesarian Sections (CS) rates higher than 10-15%”. Since then, CSs have become increasingly common in both developed and developing countries. The rate of CS has been reported to be as high as 24.5% and 25.8% among Iraqi women in the years 2009 and 2010 respectively. Objectives: The study was designed to provide data on the level of existing knowledge, attitudes and preference of modes of delivery, which can be used as a platform to raise knowledge among pregnant women and their partners and thereby empowering women to make informed choices. Patients and Methods: This cross-sectional study was undertaken in an antenatal care clinic in Baghdad Teaching Hospital, Medical City, and Baghdad from 1st Feb. -31st May 2016. All 300 pregnant attending antenatal clinic were interviewed with a structured questionnaire that solicited information on their knowledge, attitudes and preference towards modes of delivery. Results: Mean age of pregnant women was 28.3 ± 9.8SD years and84.7% were not employed. More than half of them (54.3%) had married at younger age (<20 years). Educational levels were 43.3% primary, 18% secondary and 20.4% university levels. Knowledge of majority of pregnant mothers (82.6%) about modes of delivery were obtained from relatives. Half of pregnant women had good knowledge about modes of delivery, 51.3% of them had negative attitude toward CS, and 62% had positive attitude towards CS delivery in current pregnancy. Conclusion: Study results emphasize the need for educating families, especially pregnant women and their partners about the pros and cons of different modes of giving birth to their babies.